Politik Hukum Pidana Anti Pencucian Uang Indonesia Terhadap Crypto Tumbler (Mixer) Pada Sistem Pertukaran Aset Kripto Terdesentralisasi - Olivia Agatha Kusuma; Huberto Gavra Damanik; Adela Kara Belinda (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Normatively, Crypto Tumblers are not explicitly prohibited under the Anti-Money Laundering Law, the P2SK Law, or OJK regulations, although their use may be associated with money laundering activities. Nevertheless, the automated, decentralized and cross-jurisdictional nature of crypto transactions creates significant criminal procedural challenges under both UU TPPU and KUHAP 2025. Given Crypto Tumblers positive role in protecting financial privacy, blanket criminalization is therefore inappropriate and unrealistic. Accordingly, Indonesia should adopt a graduated prohibition model through clear eligibility criteria, whitelisting by OJK and the classification of transactions involving non-compliant Crypto Tumbler users as suspicious transactions as typically monitored by PPATK.